Global Research Trends on Integrating Moral Reasoning in the Education of Future IT Professionals: A Bibliometric Analysis - Celso A. de Guzman (Future Science / FSH-PH Publications, 2026)
This paper is a bibliometric review of literature on integrating moral reasoning in information Technology (IT) education that aims to explore its publication situation, significant sources, research topic, temporal trends, and gaps in the literature. Through bibliometric techniques, the research reviewed 334 articles published in 179 sources in 1983-2025 from Scopus database. The results indicate that the sector has shown progressive growth with a rate of 4.63 per year and on average the documents are 7.37 years of age. The literature is highly conference-oriented as the majority of publications are through conference papers, which shows the rapid and practice-driven nature of knowledge dissemination. Most of the publication come from ASEE, FIE, ITICSE, ACM conference proceedings, and SIGCSE-related journals, which means that the discipline is largely influenced by engineering and computing education communities. Term-frequency output reveals that the most common terms are students, ethics, curriculum, computing education, and computer science education, indicating that the area is main concern with the incorporation of ethical knowledge and reasoning into formal education of technology. Themes that develop based on artificial intelligence, machine learning and AI ethics also show how the field reacts to modern technological trends. Some of gaps in the analysis are low international collaboration and inadequacy of research on effective pedagogical strategies to teach ethics. Overall, the findings indicate that integrating moral reasoning in IT education is an emerging and developing discipline that is relevant in equipping students with ethical consciousness, critical thinking, and professional accountability in a technological society.